3x-2(5x-y)-(4y+x)=

Simple and best practice solution for 3x-2(5x-y)-(4y+x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2(5x-y)-(4y+x)= equation:


Simplifying
3x + -2(5x + -1y) + -1(4y + x) = 0
3x + (5x * -2 + -1y * -2) + -1(4y + x) = 0
3x + (-10x + 2y) + -1(4y + x) = 0

Reorder the terms:
3x + -10x + 2y + -1(x + 4y) = 0
3x + -10x + 2y + (x * -1 + 4y * -1) = 0
3x + -10x + 2y + (-1x + -4y) = 0

Reorder the terms:
3x + -10x + -1x + 2y + -4y = 0

Combine like terms: 3x + -10x = -7x
-7x + -1x + 2y + -4y = 0

Combine like terms: -7x + -1x = -8x
-8x + 2y + -4y = 0

Combine like terms: 2y + -4y = -2y
-8x + -2y = 0

Solving
-8x + -2y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
-8x + -2y + 2y = 0 + 2y

Combine like terms: -2y + 2y = 0
-8x + 0 = 0 + 2y
-8x = 0 + 2y
Remove the zero:
-8x = 2y

Divide each side by '-8'.
x = -0.25y

Simplifying
x = -0.25y

See similar equations:

| w^2(w-3)=350 | | 5x-22=26+x | | Y^2-2y= | | 3.4+z=-7 | | -6th-7=17 | | 1/3x-1/7=8 | | x^2+38x+361=36 | | 5xy-3y+10x-6= | | x-2(x+1)=5+9 | | 15/2x+4=-2 | | 12t=16 | | 2x^2+xy-y^2=2 | | (2c)(3c)=6c | | 16340/40 | | 8*3=7x | | 15/2+4=-2 | | 36-45x+2=42x-49 | | k/3-19 | | (2x+30)=4x | | 11x-1=7x+10 | | -5(z+1)-(4z-6)=-10z | | 2n^2-n-120=0 | | 3x-8=158 | | 3(y-0.3)=19.4-y | | 2.4=t-/4.5 | | 6/3p-1=10 | | x^2+38x+361=0 | | 4+10=7A | | 5(5x+6)= | | sqrtx=1/4 | | 0=s^2+6s+10 | | 3(x-5)=6x+18 |

Equations solver categories